Resultados preliminares en la evaluación de ocho variedades de aguacate (Persea americana Mill) en zona cafetera colombiana. (1978)
At the subestación Paraguaicito (24°C of mean temperature), owned by Federación Nacional de Cafeteros de Colombia, it was carried out an experiment in colaboration with the Instituto Colombiano Agropecuario ICA, in order to evaluate eight avocado varieties, previously selected by ICA. The varieties were: "Peterson", "Trapp", "Fuchsia", "Simmonds", "Booth 8", "Booth I ", "Fairchild" and "Trinidad". Hybrids of the races Guatemala x West Indian had more vigorous growth and a bigger production than varieties of the West Indian race. "Trinidad", "Booth 1" and "Peterson" were varieties with a very vigorous growth. More produc. tive varieties (916 ton/Ha after five years of planted), were: "Peterson", "Trinidad", "Fairchild", "Trapp" and "Booth 8", "Fuchsia". "Booth 1" and "Simmonds" are discartable varieties because their low yield. By quality of the fruit were selected: "Fairchild", "Trapp", "Peterson" and "Booth 8". By considering growth of the tree, yield, fruit quality and class of the flower it is advisable to plant the variety "Booth 8" (Flower's class "B"), between varieties "Peterson" (Flower's class "A") and "Fairchild" (Flower's class "A"), at 6 x 8 m and ascribing 6 m spacing to the variety "Fairchild".